Great children's stories - Richardson, Frederick, 1862-1937. (New York : Checkerboard Press, 1972)
Contains seventeen classic stories including The Little Red Hen; The travels of a fox; The three bears; The straw ox.
Keywords: Folklore; Fairy tales; Folklore; Fairy tales